2018
DOI: 10.3835/plantgenome2017.12.0111
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Fine‐Mapping of a Quantitative Trait Locus (QTL) Associated with Embryogenic Tissue Culture Response and Plant Regeneration Ability in Maize (Zea mays L.)

Abstract: Embryogenic and regenerable tissue cultures are widely utilized in plant transformation, clonal propagation, and biological research applications. Germplasm utilized in those applications are limited, however, due to genotype-dependent culture response. The goal of this study was to identify genomic regions controlling embryogenic and regenerable tissue culture response in the globally important crop, maize ( L.), toward the long-term objective of developing approaches for genotype-independent plant genetic en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 65 publications
0
29
1
Order By: Relevance
“…Most commercially important varieties are recalcitrant or marginally transformable at present. Because culture responses for callus induction and plant regeneration are polygenic, QTL mapping and gene identification for this complex trait have been performed in Arabidopsis , rice, maize, barley, and some other crops to identify underlying genetic mechanisms ( Bolibok and Rakoczy-Trojanowska, 2006 ; Chen et al., 2007 ; Fan et al., 2012 ; Ikeuchi et al., 2013 ; Motte et al., 2014 ; Salvo et al., 2018 ). The latest breakthrough in genotype dependence is the specific expression of two major transcription factors, Wuschel2 ( Wus2 ) and Baby Boom ( Bbm ), from maize, which function as morphogenic regulators that stimulate and promote somatic cells to form embryos that develop into whole plants in a range of monocots, including maize, sorghum, sugarcane, and indica rice ( Lowe et al., 2016 ; Mookkan et al., 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Most commercially important varieties are recalcitrant or marginally transformable at present. Because culture responses for callus induction and plant regeneration are polygenic, QTL mapping and gene identification for this complex trait have been performed in Arabidopsis , rice, maize, barley, and some other crops to identify underlying genetic mechanisms ( Bolibok and Rakoczy-Trojanowska, 2006 ; Chen et al., 2007 ; Fan et al., 2012 ; Ikeuchi et al., 2013 ; Motte et al., 2014 ; Salvo et al., 2018 ). The latest breakthrough in genotype dependence is the specific expression of two major transcription factors, Wuschel2 ( Wus2 ) and Baby Boom ( Bbm ), from maize, which function as morphogenic regulators that stimulate and promote somatic cells to form embryos that develop into whole plants in a range of monocots, including maize, sorghum, sugarcane, and indica rice ( Lowe et al., 2016 ; Mookkan et al., 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, by using the F 3:4 population derived from B73 and WCIC2 (a near isogenic line of B73 containing several A188 segments), a locus associated with embryogenic and regenerative capabilities of immature embryo was fine-mapped within a 3.06 M region (chr3:178772856-181826658) based on the B73 reference genome, suggesting that the genes harbored by the A188 segment caused the high callus formation ratio (Salvo et al, 2018).…”
Section: A188 Genome-based Genetic Dissection Of Tissue Culture Responsementioning
confidence: 99%
“…Moreover, previous studies have demonstrated that changes in gene expression can be induced during somatic embryogenesis to respond to tissue culture process (Ge et al, 2017;Salvo et al, 2018;Shen et al, 2012;Zhang et al, 2014). Based on the reported transcriptome data of A188 (Zhang et al, 2014), four of the 99 A188 genes within the mapped QTL were regulated by more than 8 folds in different stages of immature embryo culture, relative to control.…”
Section: A188 Genome-based Genetic Dissection Of Tissue Culture Responsementioning
confidence: 99%
See 1 more Smart Citation
“…QTL mapping of regeneration traits has been attempted in several other cereal crops such as maize [ 104 , 105 , 106 ], wheat [ 107 , 108 , 109 ], and barley [ 110 , 111 , 112 ] ( Table 2 ). Early studies in maize using the highly and lowly regenerable A188 and B73 inbred lines identified a major QTL on chromosome 3 [ 104 ] that was recently exploited to create a germplasm with enhanced tissue culture responses, nearly isogenic to the elite B73 [ 106 ]. Fine mapping of this locus revealed a 3053-kb region containing multiple candidate genes such as ALDOLASE 1 ( ALD1 ), ZmWOX2A, and ZmWOX5B .…”
Section: Mapping Natural Variation In the Organogenic Potential Atmentioning
confidence: 99%